Le prince héritier à Sparte - Carlier, Pierre (Gerión. Revista de Historia Antigua, 2006)
In each of the two Spartan royal families, a precise dynastic nomos regulates successions. The first son who is born after his father’s accession is considered from childhood as the heir apparent. He is exempted from the agôgè; when he has reached adulthood, he may be chosen as commander-in-chief of the civic army. Such a situation, which is exceptional among Greek kingships, is probably linked with the fact that the Spartan dyarchy is an element of the constitutional kosmos of the city.